Tanda-tanda genetik biokimia dalam tiga bangsa terbesar di Semenanjung Malaysia dan Singapura: suatu penyusunan data - Tan, Soon Guan (Universiti Pertanian Malaysia, 1978)

(untitled)
A list of the data available from the scientific literature on biochemical genetic markers in Malays, Chinese and Indians from Peninsular Malaysia and Singapore was compiled. The possible uses of such data are discussed.